1997
DOI: 10.3168/jds.s0022-0302(97)76041-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between In Situ Protein Degradability and Grass Developmental Morphology

Abstract: The objective of this research was to determine the relationships between the morphological development and in situ ruminally degradable protein (RDP), ruminally undegradable protein (RUP), and microbial protein of two cool season grasses (intermediate wheatgrass and smooth bromegrass) and two warm season grasses (switchgrass and big bluestem). The initial growth of grass tillers grown near Mead, Nebraska was clipped at ground level six times during the 1992 growing season and morphologically classified. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…It is not clear why there The RDP content of C3 was 28% greater (P < 0.01) and the RUP was 55% less (P < 0.01), as a percentage of total CP, than the RDP content of C4 (Table 2). This agrees with other data indicating that cool-season forages have a greater proportion of CP as RDP and less as RUP than do warm-season forages (Mullahey et al, 1992;Mitchell et al, 1997;Coblentz et al, 2004). These data increase the body of work suggesting that cool-season forages provide more rumen-available N for fermentation and microbial protein production than do warm-season forages.…”
Section: Expsupporting
confidence: 91%
See 1 more Smart Citation
“…It is not clear why there The RDP content of C3 was 28% greater (P < 0.01) and the RUP was 55% less (P < 0.01), as a percentage of total CP, than the RDP content of C4 (Table 2). This agrees with other data indicating that cool-season forages have a greater proportion of CP as RDP and less as RUP than do warm-season forages (Mullahey et al, 1992;Mitchell et al, 1997;Coblentz et al, 2004). These data increase the body of work suggesting that cool-season forages provide more rumen-available N for fermentation and microbial protein production than do warm-season forages.…”
Section: Expsupporting
confidence: 91%
“…There have been studies comparing the ruminai degradation characteristics of moderate-to high-quality C3 and C4 forages (Mertens and Loften, 1980;Mitchell et al, 1997;Coblentz et al, 2004), but to our knowledge, this is the first study that directly compared the ruminai degradation of low-quality (<6.5% CP) cool-and warm-season forages.…”
Section: Expmentioning
confidence: 94%
“…As expected, the undegradable fraction [1)(a+b)] of CP increased with advanced stage of maturity (Table 7). The effective in situ degradation of CP decreased with advanced stage of maturity as also found in situ by Mitchell et al (1997) for different grasses, but values were only significantly different between the earliest and latest stage of development. Like previous results for DM, the NIRS predicted ED of CP was over-predicted in relation to in situ values, but values at each maturity stage were significantly different from one another.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, relatively small changes in RUP pools for maturing plants have been reported previously. Mitchell et al (1997) reported that RUP concentrations for smooth bromegrass ( Bromus inermis Leyess.) and intermediate wheatgrass [ Thinopyrum intermedium (Host) Barkworth and D.R.…”
Section: Discussionmentioning
confidence: 99%